2023
DOI: 10.1002/mp.16474
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a diode dosimeter for UHDR FLASH radiotherapy

Abstract: BackgroundUltra‐high dose rate (UHDR) FLASH beams typically deliver dose at rates of  >40 Gy/sec. Characterization of these beams with respect to dose, mean dose rate, and dose per pulse requires dosimeters which exhibit high temporal resolution and fast readout capabilities.PurposeA diode EDGE Detector with a newly designed electrometer has been characterized for use in an UHDR electron beam and demonstrated appropriateness for UHDR FLASH radiotherapy dosimetry.MethodsDose linearity, mean dose rate, and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…The SiC performance with accumulated radiation dose can also be compared with the shown by commercially available silicon diodes: for example, the signal of PTW's microSilicon detector decreases 0.5% per kGy when irradiated with 10 MeV electrons, according to the manufacturer (PTW 2019). Furthermore, the sensitivity decrease measured with a Sun Nuclear EDGE diode is 0.4% per kGy of 10 MeV electrons (Rahman et al 2023). Similar values can be extracted from the characterization of different silicon prototypes (Bruzzi 2016, Bueno et al 2022.…”
Section: Discussionsupporting
confidence: 69%
“…The SiC performance with accumulated radiation dose can also be compared with the shown by commercially available silicon diodes: for example, the signal of PTW's microSilicon detector decreases 0.5% per kGy when irradiated with 10 MeV electrons, according to the manufacturer (PTW 2019). Furthermore, the sensitivity decrease measured with a Sun Nuclear EDGE diode is 0.4% per kGy of 10 MeV electrons (Rahman et al 2023). Similar values can be extracted from the characterization of different silicon prototypes (Bruzzi 2016, Bueno et al 2022.…”
Section: Discussionsupporting
confidence: 69%
“…In most studies conducted to date, only three parameters (Ḋ m, DPP, IDR) have been set on all but the possible combinations remaining to be tested are countless. This has not been possible due to electron LINAC used for experiments that could not vary all the beam parameters linked to the FLASH effect ( 64 ). Furthermore, most of these studies ( 15 , 31 ) have used modified medical and industrial linacs to achieve UHDR, mostly by removing important components from the beam path such as the monitor chambers ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are several alternative dosimetry methods being developed to resolve the challenges of ion chambers in FLASH environments, including diamond detectors, diode dosimeters, and plastic scintillators. [63][64][65][66] Preliminary cell studies using the Clinac-FLEX system have demonstrated differential dose rate effects in normal and cancer breast cells (Figure 7). While the FLASH dose rate diminished the radiation-induced morphological changes of normal breast cells, it caused similar killing of breast cancer cells than the non-FLASH dose rate.…”
Section: Machinementioning
confidence: 99%